Sub-acute exposure of male guppies (Poecilia reticulata) to environmentally relevant concentrations of PFOA and GenX induces significant changes in the testis transcriptome and reproductive traits - C Gasparini; S Iori; E Pietropoli; M Bonato; M Giantin; A Barbarossa; A Bardhi; A Pilastro; M Dacasto; M Pauletto (Environment International, 2024)
Poly- and perfluoroalkyl substances (PFAS) are frequently detected in the environment and are linked to adverse reproductive health outcomes in humans. Although legacy PFAS have been phased out due to their toxicity, alternative PFAS are increasingly used despite the fact that information on their toxic effects on reproductive traits is particularly scarce. Here, we exposed male guppies (Poecilia reticulata) for a short period (21 days) to an environmentally realistic concentration (1 ppb) of PFOA, a legacy PFAS, and its replacement compound, GenX, to assess their impact on reproductive traits and gene expression. Exposure to PFAS did not impair survival but instead caused sublethal effects. Overall, PFAS exposure caused changes in male sexual behaviour and had detrimental effects on sperm motility. Sublethal variations were also seen at the transcriptional level, with the modulation of genes involved in immune regulation, spermatogenesis, and oxidative stress. We also observed bioaccumulation of PFAS, which was higher for PFOA than for GenX. Our results offer a comprehensive comparison of these two PFAS and shed light on the toxicity of a newly emerging alternative to legacy PFAS. It is therefore evident that even at low concentrations and with short exposure, PFAS can have subtle yet significant effects on behaviour, fertility, and immunity. These findings underscore the potential ramifications of pollution under natural conditions and their impact on fish populations.